2016
DOI: 10.1007/s00520-016-3127-0
|View full text |Cite
|
Sign up to set email alerts
|

Electronic real-time assessment of patient-reported outcomes in routine care—first findings and experiences from the implementation in a comprehensive cancer center

Abstract: Comprehensive oncological treatment needs to consider disease symptoms, quality of life, preferences, and comorbidities of individual patients in a structured, standardized, and transparent way. Our findings indicate that an adaptive, self-administered electronic assessment tool for cancer patients to report a broad set of PRO can be feasibly implemented and is well accepted by patients in a realistic setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 41 publications
2
64
1
1
Order By: Relevance
“…Patients presenting at our tertiary cancer center are often diagnosed with advanced disease [24]. Stage at diagnosis depends on the respective entity, and the predominant tumor sites in this study were gastrointestinal, seldom diagnosed at a localized stage [25].…”
Section: Introductionmentioning
confidence: 99%
“…Patients presenting at our tertiary cancer center are often diagnosed with advanced disease [24]. Stage at diagnosis depends on the respective entity, and the predominant tumor sites in this study were gastrointestinal, seldom diagnosed at a localized stage [25].…”
Section: Introductionmentioning
confidence: 99%
“…There are several advantages of ePRO, such as rapid access to data, a probable avoidance of errors during data entry, and fewer missing data in comparison with paperbased surveys and the capacity to trigger alerts or notifications for answers to special circumstances 3 and an improvement in patients' willingness to report sensitive information [23,28]. Although paperbased surveys of PRO still predominate because there are only a few reliable and validated ePRO questionnaires, numerous projects have evaluated feasibility and acceptance of HRQoL in ePRO measurement in the last few years [29][30][31][32][33][34]. Nevertheless, knowledge regarding patient acceptance, feasibility, and barriers remains limited [35], especially since hurdles might exist in relation to health status, technical skills, and socioeconomic aspects, which could influence both patients´ willingness to use ePRO and their response behavior [10,36,37].…”
Section: Electronic Measurement Of Patient-reported Outcomesmentioning
confidence: 99%
“…Large databases help to identify trends, as Siracuse and colleagues have done here. While institutions are increasingly collecting wide-ranging patientreported information in clinical practice [1,8], data collection alone will not address the elevated incidence of suicide.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…Evidence from other cancers has shown that providing appropriate early palliative care interventions and support improves quality-of-life for patients with metastatic disease [4], although this has not yet translated into a lower risk of suicide, as far as we know. There is also a need for processimprovement research, which could guide us on how to organize screening programs in ways that are clinically meaningful as well as feasible [2,3,8].…”
Section: How Do We Get There?mentioning
confidence: 99%